Protective Effects of Aqueous Extract of Piper nigrum Whole Fruits Against Tramadol-induced Hepato-and Nephrotoxicity in Wistar Rats - Nurudeen, Quadri; Abdullahi, Sulyman; Falana, Mansurat Bolanle; Asinmi, Muhammed Robiu; Dikwa, Muhammad Ali; Oweh, Oghebetega ThankGod (Journal of Science and Technology, 2024)
Tramadol, a widely used analgesic, is becoming more abused in most countries. Hence, this study aims to investigate the protective effects of aqueous extract of Piper nigrum whole fruits on tramadol-induced toxicity in male Wistar rats. Six groups (A-F) of male Wistar rats were exposed to a 14-day oral treatment. Specifically, the control group, induced group (tramadol at 60 mg/kg), reference drug group (Vitamin C at 250 mg/kg) and the extract groups (250, 500, and 1000 mg/kg). The levels of liver cellular markers ALT, AST and ALP as well as the kidney function parameters (urea, creatinine and uric acid) showed a significant (p